2010
DOI: 10.1177/0011128710382261
|View full text |Cite
|
Sign up to set email alerts
|

The Criminal Victimization–Depression Sequela

Abstract: Drawing on three waves of survey data, the authors examined the effects of criminal victimization on depression. First, the authors developed a structural equation model to determine whether criminal victimization predictsdepression. Second, recognizing that victimization is contingent on background factors, they tested whether victimization, conceptualized as an assigned treatment, has significant effects on depression, using inverse probability of treatment weighting (IPTW). In structural equation modeling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…These are sobering data for multiple reasons. There is a huge amount of evidence that sexual victimization is associated with subsequent internalizing disorders (Aday, Dye, & Kaiser, 2014;Kennedy & Prock, 2018;Turner, Finkelhor, & Ormrod, 2010), externalizing disorders (Miley, Fox, Muniz, Perkins, & DeLisi, 2020;Renner, Boel-Studt, & Whitney, 2018), impaired socioeconomic and social functioning (Hochstetler, DeLisi, Jones-Johnson, & Johnson, 2014;Kennedy & Prock, 2018), increased overall psychopathology (Najdowski & Ullman, 2009;Romano & De Luca, 2001), suicidal thoughts and behaviors (Aday et al, 2014), and, among males, becoming a sexual offender -567 (DeLisi & Beauregard, 2018;Drury, Elbert, & DeLisi, 2019;DeLisi, Kosloski, Vaughn, Caudill, & Trulson, 2014;Miley et al, 2020). Thus these victimizations are devastating to the victim and set into motion multiple, interrelated, immediate and long-term negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…These are sobering data for multiple reasons. There is a huge amount of evidence that sexual victimization is associated with subsequent internalizing disorders (Aday, Dye, & Kaiser, 2014;Kennedy & Prock, 2018;Turner, Finkelhor, & Ormrod, 2010), externalizing disorders (Miley, Fox, Muniz, Perkins, & DeLisi, 2020;Renner, Boel-Studt, & Whitney, 2018), impaired socioeconomic and social functioning (Hochstetler, DeLisi, Jones-Johnson, & Johnson, 2014;Kennedy & Prock, 2018), increased overall psychopathology (Najdowski & Ullman, 2009;Romano & De Luca, 2001), suicidal thoughts and behaviors (Aday et al, 2014), and, among males, becoming a sexual offender -567 (DeLisi & Beauregard, 2018;Drury, Elbert, & DeLisi, 2019;DeLisi, Kosloski, Vaughn, Caudill, & Trulson, 2014;Miley et al, 2020). Thus these victimizations are devastating to the victim and set into motion multiple, interrelated, immediate and long-term negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accord with studies that have found that urban African American and Latino males, particularly those of low SES, are at the highest risk for violent victimization (Conway et al, 1994; Logan et al, 2011; Rodriguez & Brindis, 1995). This finding is of concern given the high psychological and physical cost associated with experiencing violent victimization (e.g., Barker et al, 2008; Carbone-López et al, 2006; Hochstetler et al, 2010; Spikes et al, 2010). Only after age 29 was there a substantial decline in experiences of violent victimization in the HH group.…”
Section: Discussionmentioning
confidence: 99%
“…Non-fatal violent victimization is associated with a host of adverse mental and physical health outcomes, including depression, anxiety, substance abuse, and illness and disease (Barker et al, 2008; Boynton-Jarrett et al, 2008; Carbone-López et al, 2006; Gros et al, 2010; Hochstetler et al, 2010; Kilpatrick et al, 2000; Resnick et al, 1997; Schneider et al, 2011; Spikes et al, 2010). Drug use is one of the most frequent correlates of having been victimized, making this a particularly important construct to be investigated in conjunction with violent victimization (e.g., Conway et al, 1994).…”
mentioning
confidence: 99%
“…The items related to being the victim of one (or several) of the following events: a terrorist attack, a home burglary, a physical attack, and a sexual assault. The response categories were "very low" (1), "low" (2), "moderate" (3), "high" (4) and "very high" (5).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond physical injury and property loss, the experience of being a victim of a criminal act has both short-and longterm negative effects on mental health [1][2][3][4][5][6][7][8][9][10][11][12]. Although the symptoms of posttraumatic stress disorder (PTSD) are the most severe psychological sequelae of violent offenses [3,10,[12][13][14][15][16], several researchers have identified a broad spectrum of other psychological symptoms among victims of violent and nonviolent crime [2, 4, 6-10, 17, 18].…”
Section: Introductionmentioning
confidence: 99%